The Effect of Exchange Rates, Interest Rates, Inflation, Net Exports on Economic Growth in Indonesia - Mala, Said; Hatim, Fajri; Hasim, Daud (Global Economic, Social, and Development Review, 2024)
The steady transformation of a nation's economy toward improved circumstances over a given time frame is known as economic growth. It can be characterized as a rise in national income corresponding to an economy's increased capacity for production. This study examines the partial and simultaneous effects of inflation, net exports, Interest rates currency rates on Indonesia's economic development between 2015 and 2023. The data used in this study were secondary quarterly time series data from Indonesia from 2001 to 2023. Analysis is done using Ordinary Least Squares (OLS). The findings show that the currency exchange rate, SBI interest rates, inflation, and net exports all have a significant impact on Indonesia's economic growth, both separately and in combination.